2013
DOI: 10.1016/j.neuropharm.2012.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid facilitation of fear extinction memory recall in humans

Abstract: A first-line approach to treat anxiety disorders is exposure-based therapy, which relies on extinction processes such as repeatedly exposing the patient to stimuli (conditioned stimuli; CS) associated with the traumatic, fear-related memory. However, a significant number of patients fail to maintain their gains, partly attributed to the fact that this inhibitory learning and its maintenance is temporary and conditioned fear responses can return. Animal studies have shown that activation of the cannabinoid syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
3
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 92 publications
(143 reference statements)
7
123
3
4
Order By: Relevance
“…By contrast, Rabinak et al (2013) observed enhanced extinction memory retention when THC was administered, but no immediate effects on extinction learning. This effect might be mediated by increased activity in the basolateral part of the amygdala, the prefrontal cortex and hippocampus during extinction memory recall, brain structures centrally involved in extinction learning (Rabinak et al, 2014).…”
Section: Discussionmentioning
confidence: 68%
“…By contrast, Rabinak et al (2013) observed enhanced extinction memory retention when THC was administered, but no immediate effects on extinction learning. This effect might be mediated by increased activity in the basolateral part of the amygdala, the prefrontal cortex and hippocampus during extinction memory recall, brain structures centrally involved in extinction learning (Rabinak et al, 2014).…”
Section: Discussionmentioning
confidence: 68%
“…The compound disrupts the reconsolidation of a contextual fear memory in a manner dependent on activation of CB1 located in prelimbic subregions of the medial prefrontal cortex and on memory retrieval/reactivation (823). In humans, oral dronabinol prevents the recovery of fear (706).…”
mentioning
confidence: 99%
“…The next day, participants were treated with placebo or dronabinol 2 h prior to an extinction session. Those treated with dronabinol had less reinstatement of fear responding 24 h later relative to the placebo group (Rabinek et al, 2013). Given that exposure therapy to treat PTSD is often associated with poor extinction retention (eg, Milad et al, 2009), these data suggest that cannabinoid administration during extinction training might reduce the reinstatement of fear responding.…”
Section: Ptsd Meg Haneymentioning
confidence: 85%